Experimental and Numerical Evaluation of the Ablation Process of Carbon/Carbon Composites Using High Velocity Oxygen Fuel System - Xueling Fan; Peng Jiang; Biao Li; Xiaochao Jin; Yong Zhao (Advances in Materials Science and Engineering)
The ablation process of carbon/carbon (C/C) composites was tested under hypersonic flowing propane flame. The microstructures of C/C composites were characterized and the numerical analysis was performed. Two typical ablation morphologies of the carbon fibers, which are drum-like and needle-like shapes, were observed depending on the alignments of fibers to the flame directions. Temperature fields in the composites were analyzed using finite element method, and the mechanisms that govern the formation of different ablation behaviors were elucidated. For paralleled fiber bundles, the highest temperature situates in the middle parts underlying the ablation pits, where the drum-like shape is formed. For perpendicular fiber bundles, the highest temperature appears at the turning point between the transverse section and the surface of fiber, which leads to the gradual ablation from the fiber surface toward the axis, and eventually the formation of the needle-like shape.